Edukasi Stunting melalui Emo Demo “Camilan O’ke” pada Ibu Balita di Desa Bulak, Rowosari, Kendal - Nafilah; Ardian Candra Mustikaningrum; Eliyana; Ananda Desfa Syahrani; Angela Putri Aprilliani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Stunting in toddlers is still a special concern, especially in Kendal Regency. One of the causes of stunting is the mother's knowledge about providing inappropriate complementary feeding. In fact, Kendal Regency has local food ingredients in the form of mackerel which is an alternative to prevent stunting. Therefore, it is necessary to increase the mother's knowledge about the use of local food sources in preventing stunting. The purpose of this Community Service activity is to increase knowledge by providing Stunting Education through the "O'KE" Snack Demo for Toddler Mothers in Bulak Village, Rowosari, Kendal. The method in this activity is a lecture and an emo demonstration of making meatball snacks made from mackerel. Mothers of toddlers were also given a questionnaire to determine the knowledge score before and after the activity. The results of the data collection were analyzed using the Wilcoxon test (p≤0.05). The results of the activity showed a significant increase in the average score before (81±9.1) and after the emo demo activity (100±0.0). These results prove that providing stunting education through emo demos is effective in increasing the knowledge of mothers of toddlers. The demo given is expected to train mothers in processing fish-based snacks to prevent stunting in toddlers. Thus, toddlers can grow optimally.